Kisah Selera dari Negeri Rempah: Memahami Gastrodiplomasi dari Perspektif Indonesia - Baskoro, Riski M. (Indonesian Perspective, 2022)
The paper complements various theories and practices that have been elaborated by gastrodiplomasi experts and it is also a prolongation of my previous published paper by the theme of conceptualization in gastrodiplomasi. This paper emphasizes on the context of Indonesian gastrodiplomasi. This paper aims to trace back the origins of gastrodiplomasi in Indonesian history. The study found that gastrodiplomasi is an elusive theory where many people fail to understand it holistically. In addition, the savory of Nusantara, as the root of Indonesian gastrodiplomasi, cannot be separated from the role of spices which has been quested for many foreign explorers for hundred years ago.